Endovascular treatment of posterior inferior cerebellar artery aneurysms: a 7-year single-center experience. (21st June 2016) - Xu, Feng; Hong, Yong; Zheng, Yongtao; Xu, Qiang; Leng, Bing
Abstract : Aim: To report our experience with endovascular treatment of posterior inferior cerebellar artery (PICA) aneurysms. Methods: Between January 2007 and December 2014, 40 patients with 42 PICA aneurysms were treated with endovascular embolization at our institution. Twenty-eight patients had 29 saccular aneurysms and 12 patients had 13 fusiform/dissecting aneurysms. The endovascular modalities were: (1) selective occlusion of the aneurysm with or without stent assistance (n=19); (2) occlusion of the aneurysm and the parent artery (n=22); and (3) occlusion of the aneurysm including the vertebral artery and PICA origin (n=1). Specifically, selective embolization was performed in 93.3% of aneurysms (14/15) proximal to the telovelotonsillary segment. Results: Immediate angiographic results included 31 complete occlusions (74%), 3 nearly complete occlusions (7%), and 8 incomplete occlusions (19%). Mean follow-up of 20 months in 31 aneurysms showed 27 stable results, 3 further thromoboses, and 1 recurrence. Final results included 27 complete occlusions (87.1%) and 4 incomplete occlusions (12.9%). There were 5 overall procedural-related complications (12.5%), including 1 infarction (2.5%) and 4 intraprocedural ruptures (10.0%). Procedure-related morbidity and morbidity was 5.0% (2/40) and 2.5% (1/40), respectively. Clinical outcome was excellent (Glasgow Outcome Scale 5 in 31 of 33 patients at long-term follow-up). Conclusions: PICA aneurysms may be effectively treated by different endovascular approaches with favorable clinical and radiologic outcomes. Further studies are required to compare the safety and efficacy of endovascular treatment with open surgery.